Proactive Coping As A Suicide Protective Factor In Adolescents: A Systematic Review - Dutya Intan Larasati; Ah Yusuf; Sestu Retno Dwi Andayani (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Suicidal behavior in adolescents is a serious public health problem. Adolescents have a lot of psychological conflicts when solving their problems, so they need effective coping strategies to deal with stressors. Purpose: This systematic review aimed to determine the proactive coping function to prevent suicidal behavior in adolescents. Comprehensive journal search including cross-sectional study design from several databases namely Scopus, Science Direct, PubMed, ProQuest, and EBSCO are used for scientific contributions published in 2017-2021. This systematic review uses PRISMA. Proactive coping is future-oriented to prepare adolescence for stress to prevent suicidal behavior as a result. Proactive coping facilitates self-control of negative behavior (26.7%), improves psychological conditions (40%), and increases welfare and life satisfaction (33,3%).Proactive coping increases self-protection by shifting the focus of risk behavior to more effective. The use of proactive coping has the potential to be a protective factor against suicidal behavior in adolescents